Social networks: applicability to minority communities in multilingual settings - SUBRA GOVINDASAMY and MOHANA NAMBIAR (Int'l. J. Soc. Lang. 161 (2003), pp. 25-45, 2003)
Milroy(1987) has suggested that a close-knit social network system is a significant device of language maintenance and that in principle it can be applied universally. However, local researchers such as David's (1996) study of the Sindhi community in Malaysia show that although the community has a close and dense network, it is moving away from its ethnic language. This study set out to examine to what extent constructs from the West such as social networks would be applicable to minority, immigrant communities like the Malayalees in the context of multilingual Malaysia. The study shows that although there is a dense network system operating in the community (albeit slowly declining with age of members), it has not facilitated language maintenance. Malayalees are still interacting socially with more of their own kind than with members of other ethnic groups, but the language of interaction is increasingly shifting from Malayalam to English. Hence it appears that in the present era where the priority is on economic advancement, patterns of social interaction such as the networks system is unable to act as a norm enforcement agent as the community, particularly the immigrant minority, responds to the opportunities and pressures of its external environment.